Towards Intelligent-TPACK: An empirical study on teachers’ professional knowledge to ethically integrate artificial intelligence (AI)-based tools into education - Celik, Ismail (Computers in human behavior, 2023)
The affordances of artificial intelligence (AI) have not been totally utilized in education. To effectively integrate AI into education, teachers’ AI-specific technological and pedagogical knowledge is important. Furthermore, due to novel ethical issues caused by Al, teachers also must have the knowledge to assess AI-based decisions. None of the previous studies so far explored teacher knowledge to pedagogically and ethically use AI-based tools. Considering this gap, we first developed a scale to measure the knowledge for instructional AI use based on the technological, pedagogical, and content knowledge (TPACK) framework. We extended TPACK with ethical aspects. Secondly, we built a model to investigate the interplay of TPACK components and ethics. The results indicated that as long as teachers have more knowledge to interact with AI-based tools, they will have a better understanding of the pedagogical contributions of AI. Further, technological knowledge (TK) allows teachers to better assess decisions of AI. However, only TK is not sufficient educational integration of AI-based tools. For teachers to deploy AI in education efficiently, TK is meaningful when it is combined with pedagogical knowledge (PK), reflected in technological pedagogical knowledge (TPK). Given pedagogical and technological affordances of AI-based tools, the current study suggests the Intelligent-TPACK framework. •A scale was developed for measuring teachers' knowledge for AI-based instruction.•TPACK framework is extended with the knowledge on ethical assessments.•Technology knowledge (TK) is a positive predictor of ethical assessments, but not of TPACK.•Technological and pedagogical knowledge (TPK) is crucial to integrate AI-based tools.•The ethical assessment is as effective as TPK in the influencing TPACK.